THE EFFECT OF ICT ASSISTED PROJECT-BASED LEARNING AND LEARNERS SELF-DIRECTION ON WRITING COMPETENCY OF SOPHOMORE STUDENTS OF THE INTERNATIONAL BALI HOTEL SCHOOL DENPASAR - DIAN SAWITRI, NI LUH PUTU (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Â Sawitri, Dian Ni Luh Putu (2012), The Effect of ICT assisted Project Based Learning (PBL) and Learners Self Direction on Writing Competency of Sophomore Students of The International Bali Hotel School Thesis, English Education, Postgraduate Program, Ganesha University of Education. This thesis has been approved and corrected by supervisor I: Dra. Luh Putu Artini, M.A.,Ph.D. and Supervisor II: Dr. Ni Made Ratminingsih, M.A. Keywords: ICT based PBL, self-directed learning, writing competency. The aim of this study was to prove whether the implementation of ICT based PBL and the studentsâ self-directed learning give a significant effect to the studentsâ writing competency. The study was a quasi-experimental study by applying 2 x 2 factorial design. The population was 5 classes (128 students) of sophomore students of the International Bali Hotel School in academic year 2011/2012, in which 4 classes were taken as samples which were then assigned into two different groups; experimental group and control group, by Random Sampling to a class(intact group). The research data were collected through questionnaire and test and that the result was then analysed using Statistical Two-Way Anova and Tukey test. The results show that, first, there was a significant effect of ICT based PBL strategy on students writing competency, in which the students who were taught using ICT based PBL have higher writing competency than those who were taught by using conventional teaching strategy. Secondly, there was a significant interaction between self-directed learning and ICT based PBL. Third, there was a significant difference on studentsâ writing competency taught using ICT based PBL strategy with high level of self-directed learning, where students with high level of self-directed learning performed better when they were taught using ICT based PBL strategy rather than conventional teaching strategy. Fourth, there was a significant difference between the writing competency of the students with low level of self-directed learning when they were taught by using ICT based PBL compared to those students taught using conventional teaching, in which it was found that conventional teaching was more effective to students with low level of self-directed learning. Students taught using conventional teaching strategy yielded better result in writing competency compared to those treaded using ICT based PBL strategy. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRAK Â Sawitri, Dian Ni Luh Putu (2012), Pengaruh Pembelajaran Berbasis Proyek degan Bantuan Teknologi Komunikasi dan Informasi serta Tingkat Kemandirian dalam Belajar terhadap Kemampuan Menulis Siswa Semester Dua Sekolah Tinggi Perhotelan Bali International Denpasar. Thesis, Jurusan Pendidikan Bahasa, Program Pasca Sarjana, Universitas Pendidikan Ganesha. Thesis ini telah diperiksa dan disetujuiÂ oleh pembimbing I: Dra. Luh Putu Artini, M.A.,Ph.D. dan pembimbing II: Dr. Ni Made Ratminingsih, M.A. Kata kunci: ICT based PBL, self-directed learning, writing competency Â Tujuan penelitian ini adalah untuk membuktikan apakah penerapan pembelajaran berbasis proyek dengan bantuan ICT dan kemandirian dalam belajar berperngaruh secara signifikan terhadap kemampuan menulis siswa semester dua Sekolah Tinggi Perhotelan Bali Internasional. Penilitian ini dirancang dalam bentuk ekperimen dengan menerapkan desain 2x2 faktorial. Sampel dalam penelitian ini melibatkan empat kelas Management Perhotelan yang diambil dari populasi 5 kelas siswa semester dua divisi Management Perhotelan. Data dalam penelitian ini dikumpulkan melalui tes dan kuisioner. Berikutnya data dianalisis dengan menggunakan analisis two-way ANOVA dan tes Tukey yang berhasil merumuskan beberapa hasil sebagai berikut. Pertama, terdapat perbedaan signifikan antara kemampuan menulis siswa yang diajar menggunakan teknik pembelajaran berbasis proyek dengan bantuan ICT dibandingkan dengan hasil kemampuan menulis siswa yang diajar menggunakan teknik konvensional. Kedua, terdapat perbedaan kemampuan menulis siswa yang memiliki kemandirian belajar yang tinggi yang diajar melalui teknik pembelajaran berbasis proyek dengan bantuan ICT dibandingkan dengan teknik konvensional. Ketiga, terdapat perbedaan signifikan dalam kemampuan menulis siswa yang memiliki kemandirian belajar yang rendah ketika diajar dengan teknik pembelajaran berbasis proyek dengan bantuan ICT dan teknik konvensional. Siswa dengan kemandirian belajar rendah memiliki hasil menulis lebih baik ketika diberikan memalui teknik konvensional. Keempat, terdapat interaksi antara kemandirian belajar dengan teknik pembelajaran berbasis proyek dengan bantuan ICT.